Designing, Implementation and Evaluation of the OSCE Exam for Psychiatric Assistants Based on the Topics of the Educational Curriculum - Farzan KHeyrkhah; SUsan Moudi; Angela Hamidia; Romina Hamzehpour; Sekineh Javadian; Mahbobeh Khozan; Atefeh Mosavi; Sodabeh Alidadi (Babol University of Medical Sciences, 2021)
Background and Objective: Teaching, learning and evaluation in the field of psychiatry has always been considered. During the psychiatric assistantship course, learning the skill of interviewing the patient and prescribing appropriate therapies is one of the highest educational priorities. In this study, an attempt has been made to investigate the effect of the Objective Structured Clinical Exam (OSCE) on improving the skills of residents. Methods: In this cross-sectional study from the academic year 2015-2016 to 2009-2010, all psychiatry residents were tested weekly by the OSCE method according to the curriculum topics. After the test, the satisfaction of professors and residents was assessed using a questionnaire. Also, the scores of these tests were compared with the scores at the end of the year. Findings: The mean scores of residents for OSCE and end-of-year exams were 21 ± 3.04 and 125.54 ± 18.48, respectively. Pearson correlation coefficient for the relationship between OSCE score and end-of-year score during these 4 consecutive academic years was r = 0.830 and P <0.001. The results of the survey of professors and assistants showed a high level of satisfaction with the tests. Conclusion: The relationship between end-of-year scores and OSCE test scores and the results shown in the success of residents in the specialized board exam is evidence of the success of the design and implementation of the OSCE method to improve the skills of residents in OSCE evaluation.